Quasi-guided and photonic modes in 2D macroporous silicon structures with SiO2 nanocoatings. - Sapelnikova, O.; Karachevtseva, L.; Lytvynenko, O.; Parshyn, K.; Wrang Bo (Xiмiя, Фiзикa ma mexнoлoгiя noвepxнi., 2015)
We investigated the IR light absorption oscillations in 2D macroporous silicon structures with SiO2 nanocoatings 70-800 nm thick. The Wannier-Stark electro-optical effect due to the strong electric field on Si-SiO2 interface and an additional electric field of quasi-guided optical modes were analyzed. The photonic modes and band gaps were also considered as peculiarities in absorbance spectra of macroporous silicon structures with a thick SiO2 nanocoating.
Keywords: macroporous silicon; SiO2 nanocoatings; quasi-guided and photonic modes; department of physics; 538.951